시니컬 리얼리즘과 인민의 얼굴들, 몸 - 김영미; Kim Young Mi (중국연구, 2019)
Cynical Realism is an idiom created consciously by Li Xianting, a Chinese contemporary art critic under a clear purpose of wanting to inform the Chinese art industry earnestly along with the creation of idioms like 'Political Pop Art' and 'Gaudy Art'. The paths of these terms were mainly through magazines and the Venetian and Sao Paulo Biennale in Brazil which were done in 1993, 1995 and 1997, and the works exhibited here were sold in each market of the world art since mid-2000. This led China's contemporary art to enter the capitalist line, and virtual realism became the most “Chinese” part of Chinese contemporary art by selling it at the highest price. In particular, these cynical realism artists who were educated in the socialist era wanted to open a new socialist art in the post-socialist era were people like li Wei, Fang Lijun, Zhang Xiaogang, Yue Minjun, and Zheng Fanzhi. The characteristics are as follows. First, they focus on the 'face'. This confirms the status in which art was used in the last socialist period. It represents important symbols in post-socialist China by replacing the face of the present people in the portraits of Mao Zedong. Second, 'family' stands out as the identity of the individual and stands at the crossroads of 'people', a member of the socialist era. This is read as a movement to push out the existence of 'workers, peasants, soldiers' who existed only as constituent members of socialism in the past socialism, and to find their identity in the family members. Third, they pay attention to ‘emotion’ such as laughter or depression. This is also is in contrast to Mao's expressionlessness. which was the face of a public hero during the socialist era. The face of the people in the post-socialist era is just one person who is in the process of being happy. Especially, their emotions need attention because they are laughters and depressions that are pretended expressions rather than direct expressions. The post-Socialist “people” were now different from the positions of the socialist people. They have evolved into many classes, and in the present situation, the people are actually in contact with the so called "social lows" after 2000.Thus, it can be said that the cynical realism is a realistic demonstration of the fact that the term "people" which was used in the socialism period, should be reconsidered.